If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11(x + -9) = -3 + -8 Reorder the terms: 11(-9 + x) = -3 + -8 (-9 * 11 + x * 11) = -3 + -8 (-99 + 11x) = -3 + -8 Combine like terms: -3 + -8 = -11 -99 + 11x = -11 Solving -99 + 11x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '99' to each side of the equation. -99 + 99 + 11x = -11 + 99 Combine like terms: -99 + 99 = 0 0 + 11x = -11 + 99 11x = -11 + 99 Combine like terms: -11 + 99 = 88 11x = 88 Divide each side by '11'. x = 8 Simplifying x = 8
| 5(3X-6)=-6(2X-4) | | 3m+6hm= | | -5x-13=-13 | | 79=2*3.14r | | -44m(m+3)=24 | | 5x+(6x-15)= | | -6x+8*3=18 | | 80=2*3.14r | | r-15=1.5 | | X^3-3X^2-16X+6=0 | | 3(2n-5)=1/2(-12n+30) | | 2x=7x^2 | | 4x-183=69-10x | | 3x-2.1=4.5 | | n^2+10n+16= | | 7(5+-10)=67 | | -3(5+-10)=67 | | 4x^2-28x+49*(2x-7)=0 | | 3x+2y=2x+8 | | 2(h+2)+4h=-10 | | x=22.75 | | 7+-15+-10=67 | | 152=3x+4(2x+16) | | 6-353937-173= | | 0=144-16t^2 | | 5x+1=4y+7 | | 3(2x+11)=6x+23 | | 56-5z=-184 | | 7a+b-8= | | 139=-5+3(8+8r) | | 3+4x-7+a=-5 | | 4y-5-1-y= |